Cost of Cerebellar Ataxia in Hong Kong: A Retrospective Cost-of-Illness Analysis - Stanley, Winser John; Kelly, Chan Kit Laam; Tung, Chinn Ching; Lok, Tang Wai; Ringo, Tye Man Kit; Ho, Yeung Kai; Cheung, Raymond (Frontiers in Neurology, 2020)
Background: Cerebellar ataxia affects the coordination and balance of patients. The impact of this disease increases burden in patients, caregivers and society. Costs and the burden of this disease have not been investigated in Hong Kong. Objectives: (1) To estimate the socioeconomic cost of cerebellar ataxia in Hong Kong for the base year 2019, (2) to assess the health-related quality of life (HRQoL) and severity of ataxia and (3) to establish the correlation between the severity and cost of cerebellar ataxia and to examine the correlation between the severity of cerebellar ataxia and HRQoL. Methods: A retrospective cross-sectional study was conducted amongst 31 patients with cerebellar ataxia. Cost-related data were obtained through self-reported questionnaires. The severity of ataxia was assessed using the Scale for Assessment and Rating of Ataxia, and HRQoL was assessed using the Short Form (36) Health Survey (SF-36). Pearson correlation was used for normally distributed data, whereas Spearman correlation was used otherwise. Results: The mean severity of ataxia was 21 out of 40. The average direct and indirect costs of a patient with ataxia in 6 months were HKD 51,371 and HKD 93,855, respectively. The mean difference between the independent to minimally dependent in activities of daily living (ADL) group and the moderate to maximally dependent in ADL group for direct and indirect costs was HKD 33,829 and HKD 51,444, respectively. Significant expenditure was related to production lost (42%), caregiver salary (17%) and in-patient care (16%) . The physical functioning (r=−0.58) and general health (r=−0.41) of SF-36 were negatively correlated with disease severity (p<0.05). A significant, positive correlation was found between disease severity and direct cost (Spearman’s rho=0.39) and the cost of hiring a caregiver (Spearman’s rho=0.43). Conclusion: The mean cost for 6 months for patients with cerebellar ataxia in Hong Kong is HKD 146,832. Additional support, including employment, access to specialist consultants, informal home care and community participation, are some areas that should be addressed. Future study on a larger population with a prospective design is necessary to confirm the aforementioned claims.